(untitled) (Bangladesh Journal of Medical Science, 2015)
Introduction: Osteoarthritis of the knee is a common orthopaedic condition. Medial compartment osteoarthritis results from undue stress on the medial compartment of the knee joint following varus deformity. High tibial osteotomy (HTO) has been a long-standing treatment for osteoarthritis of the medial compartment of the knee. Although knee replacement has gained wide popularity for its treatment, still HTO is a good and cost effective procedure for young patients having good range of motion and uni-compartmental involvement. Objective: To evaluate the results of HTO in medial compartment osteoarthritis. Methods and Material: This study was conducted in a tertiary care teaching hospital of North India over a period of 3 years. The patients with disabling knee pain due to medial compartment osteoarthrosis with genu varus deformity refractory to conservative treatment were treated by High Tibial Osteotomy. Results: Overall 40 patients with medial compartmental osteoarthritis were treated with HTO. Patients were evaluated for the severity of pain as per Visual Analogue Score (VAS). There was satisfactory pain reduction (up to 80%) in most of the patients. Conclusions: HTO is a good procedure for young patients with good range of motion and changes confined to one compartment only. Bangladesh Journal of Medical Science Vol.14(4) 2015 p.389-392